Sustaining grant-funded programs: Conditions for sustaining initiatives that enhance diversity in STEMM - Naomi A. Stephen; Krystle P. Cobian; Ana L. Romero; Hector V. Ramos; Sylvia Hurtado (PLoS ONE, 2026)
As funding agencies seek to broaden their impact in science, technology, engineering, mathematics, and medicine (STEMM) and workforce diversity, many grants have required plans for sustaining institutional change beyond the grant-period. However, little is known about the types of STEMM interventions that are likely to be sustained. Employing a multiple case study design, we examine the NIH BUilding Infrastructure Leading to Diversity (BUILD) initiative, at 10 awarded higher education sites nationwide, designed to promote sustainable change in biomedical workforce diversity. Among all the activities developed by program sites, undergraduate research training, faculty mentoring training, and curricular changes were most likely to be sustained in the final two years of the 10-year award period. Drawing on implementation science, we also examined why interventions were sustainable and identified four contextual elements that largely facilitated program sustainability: institutional financial status; organizational infrastructure and partnerships; central administration and STEMM faculty commitment; and alignment with institutional priorities. Ultimately, this study provides key lessons for future grant-funded teams and senior administrators engaged in efforts to promote equity and inclusion in STEMM.